Severe infections in neurocritical care. Issue 2 (April 2021) - Martin-Loeches, Ignacio; Blake, Alan; Collins, Daniel
Abstract : Purpose of review: We have highlighted the recent advances in infection in neurocritical care. Recent findings: Central nervous system (CNS) infections, including meningitis, encephalitis and pyogenic brain infections represent a significant cause of ICU admissions. We underwent an extensive review of the literature over the last several years in order to summarize the most important points in the diagnosis and treatment of severe infections in neurocritical care. Summary: Acute brain injury triggers an inflammatory response that involves a complex interaction between innate and adaptive immunity, and there are several factors that can be implicated, such as age, genetic predisposition, the degree and mechanism of the injury, systemic and secondary injury and therapeutic interventions. Neuroinflammation is a major contributor to secondary injury. The frequent and challenging presence of fever is a common denominator amongst all neurocritical care patients.